2005
DOI: 10.1089/cap.2005.15.477
|View full text |Cite
|
Sign up to set email alerts
|

The Presentation of Anxiety in Children with Pervasive Developmental Disorders

Abstract: Anxiety appears to be a clinically important concern in many children with PDD. Similarities in anxiety symptom presentation and their association with psychotic symptoms in both children with and without PDD support the possibility of: (1) psychiatric comorbidity in the former; (2) at least some overlap in causal mechanisms for anxiety and psychotic symptoms in both PDD and non-PDD children; and (3) a unique diagnostic entity comprised of PDD, anxiety, and psychotic symptoms. Lastly, clinicians should serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
156
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(178 citation statements)
references
References 31 publications
15
156
2
5
Order By: Relevance
“…Scoring this parent-rated scale in the standard fashion showed that 43 percent of the subjects met the CASI screening cut-off criteria for one or more of the six DSM-IV anxiety disorders. This number of children with PDD who met the screening symptom criteria of anxiety disorders is twice as high as the 20 percent estimates of the lifetime prevalence rates of pediatric anxiety disorders in the general population (Costello et al 2005;Shaffer et al 1996) and similar to the estimates of frequency of anxiety problems in other studies of children with PDD (Gadow et al 2004Muris et al 1998;Sverd 2003;Weisbrot et al 2005). The 20-item anxiety measure derived of the CASI items, demonstrated good internal consistency in children with or without cognitive impairment.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Scoring this parent-rated scale in the standard fashion showed that 43 percent of the subjects met the CASI screening cut-off criteria for one or more of the six DSM-IV anxiety disorders. This number of children with PDD who met the screening symptom criteria of anxiety disorders is twice as high as the 20 percent estimates of the lifetime prevalence rates of pediatric anxiety disorders in the general population (Costello et al 2005;Shaffer et al 1996) and similar to the estimates of frequency of anxiety problems in other studies of children with PDD (Gadow et al 2004Muris et al 1998;Sverd 2003;Weisbrot et al 2005). The 20-item anxiety measure derived of the CASI items, demonstrated good internal consistency in children with or without cognitive impairment.…”
Section: Discussionsupporting
confidence: 70%
“…Larger samples of children with PDD have also shown that externalizing and internalizing psychopathology are common when examined dimensionally (Lecavalier 2006) or categorically (Gadow et al 2004Leyfer et al 2006;Weisbrot et al 2005). Furthermore, Gadow et al (2004) showed that the levels of psychiatric symptoms in children with PDD were similar to those in psychiatrically referred children without PDD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of ODD/ADHD groups in the ASD versus clinic and community control samples indicated few between-sample differences in the relative severity of co-occurring symptoms in ODD/ADHD groups, which suggests that similar processes may explain at least some of the ODD/ADHD syndrome differentiation in all three samples. Although these analyses are exploratory, this interpretation is supported by similar results for ADHD subtypes (Gadow et al 2006), anxiety and psychotic symptoms (Weisbrot et al 2005), sleep problems (DeVincent et al 2007), and tics .…”
Section: Discussionmentioning
confidence: 61%
“…For example, sleep problems can exacerbate and worsen repetitive and stereotypic behaviors, 51 inattention and hyperactivity, and other problematic daytime behaviors. [52][53][54] Sleep problems can also interfere with learning …”
Section: Figurementioning
confidence: 99%